2021
DOI: 10.1002/adfm.202105354
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Interfacial Reduction Kinetics and Suppressing Electrochemical Oscillations in Li4Ti5O12 Thin‐Film Anodes

Abstract: Understanding the fundamentals of surface decoration effects in phase‐separation materials, such as lithium titanate (LTO), is important for optimizing the lithium‐ion battery (LIB) performance. LTO polycrystalline thin‐film electrodes with and without doped Al–ZnO (AZO) surface coating decoration are used as ideal models to gain insights into the mechanisms involved. Operando shear force modulation spectroscopy is used to observe for the first time the nanoscale dynamics of solid‐electrolyte‐interphase (SEI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…The presence of amorphous alumina and the substitution of Zn 2+ by Al 3+ ions can account for these changes, which lead to increased lattice disorder and a decrease in the crystalline lattice constant. The findings are consistent with previous reports. , The inverse fast Fourier transform (FFT) technique, utilizing Digital Micrograph, is utilized to isolate and filter the square region corresponding to the AZO/WO 3 thin film. The high-resolution TEM (HRTEM) image reveals lattice fringes of 0.169, 0.078, 0.092, and 0.240 nm.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The presence of amorphous alumina and the substitution of Zn 2+ by Al 3+ ions can account for these changes, which lead to increased lattice disorder and a decrease in the crystalline lattice constant. The findings are consistent with previous reports. , The inverse fast Fourier transform (FFT) technique, utilizing Digital Micrograph, is utilized to isolate and filter the square region corresponding to the AZO/WO 3 thin film. The high-resolution TEM (HRTEM) image reveals lattice fringes of 0.169, 0.078, 0.092, and 0.240 nm.…”
Section: Resultssupporting
confidence: 90%
“…The findings are consistent with previous reports. 38,39 The inverse fast Fourier transform (FFT) technique, utilizing Digital Micrograph, is utilized to isolate and filter the square region corresponding to the AZO/ WO 3 thin film. The high-resolution TEM (HRTEM) image reveals lattice fringes of 0.169, 0.078, 0.092, and 0.240 nm.…”
Section: Xps Of the Thin Filmsmentioning
confidence: 99%
“… 5 Chen et al reported that the charge/discharge oscillations of Li 4 Ti 5 O 12 electrodes were suppressed by doped Al-ZnO surface coatings decoration, which can reduce barriers to surface nucleation. 13 Lim et al revealed the memory effect as well as the electrochemical oscillation of Li 4 Ti 5 O 12 with oxygen defects on the surface. 14 And we have reported the electrochemical oscillation in an Al-doped Li 4 Ti 5 O 12 composite, that has an ultra-high Al content far beyond the saturation doping concentration to form Al 2 O 3 phase.…”
Section: Introductionmentioning
confidence: 99%
“…The inserted Li atoms occupy octahedral 16c sites and as a result of coulombic interaction between tetrahedral sites (mutual repulsive force between newly inserted and initially present Li + ions) cause the migration of Li + ions present in the tetrahedral 8a site to octahedral 16c sites in a two-phase separation mechanism with partial reduction of Ti 4+ to Ti 3+ ions. Thus, the material exhibits a theoretical discharge capacity of $175 mA h g −1 , which operates between the de- [20][21][22][23] The equation of the reaction can be represented as:…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the material exhibits a theoretical discharge capacity of ∼175 mA h g −1 , which operates between the de-lithiated spinel state Li 4 Ti 5 O 12 and lithiated rock salt state Li 7 Ti 5 O 12 . 20–23 The equation of the reaction can be represented as:(spinel LTO)Li 4 Ti 5 O 12 + 3Li + + 3e − ↔ Li 7 Ti 5 O 12 (rock salt LTO)However, both spinel and rock salt states of LTO display very similar lattice parameters with ∼0.77% lattice shrinkage in the lithiated phase (Li 7 Ti 5 O 12 ; Fm 3̄ m ). In addition to cycling stability and safety, factors such as low-cost precursors and easy fabrication methods made LTO an attractive LIC anode.…”
Section: Introductionmentioning
confidence: 99%